A step by step of content validity assessment process on approach towards safety knowledge, safety climate and SMEs safety performance framework - Nor Azma Rahlin; Ayu Suriawaty @ Siti Aisyah Bahkia; Zainudin Awang; Roslida Abdul Razak; Sidah Idris (Curtin Business School, 2021)
This article examines the issues and the conceptual basis in the operationalized definition of safety knowledge. The importance of safety knowledge emphasizes the mediation role of safety knowledge in the indirect link between safety climate and safety performance assessment in small and medium enterprises and the functional nature of content validity by applying a step-by-step content validity assessment. A content validation assessment process aims to increase representativeness, relevancy, clarity, comprehensiveness of the measurement's validity besides to ensure the instrument answers the research question. In business, social science, and management science, many variables of interest and research outcomes are abstract concepts and its function by robust theoretical and conceptual explanation. Thus, a step-by-step content validity assessment offered a bridge to achieve a valid and reliable measurement, and it was an essential element of quality research.